Reciprocal Effect of Copper and Iron Regulation on the Proteome of Synechocystis sp. PCC 6803 - Zhen, Zhang-He; Qin, Song; Ren, Qing-Min; Wang, Yu; Ma, Yu-Ying; Wang, Yin-Chu (Frontiers in Bioengineering and Biotechnology, 2021)
Cyanobacteria can acclimate to changing copper and iron concentrations in the environment via metal homeostasis, but a general mechanism for interpreting their dynamic relationships is sparse. In this study, we assessed growth and chlorophyll fluorescence of Synechocystis sp. PCC 6803 and investigated proteomic responses to copper and iron deductions. Results showed that copper and iron exerted reciprocal effect on the growth and photosynthesis of Synechocystis sp. PCC 6803 at combinations of different concentrations. And some proteins involved in the uptake of copper and iron and the photosynthetic electron transport system exhibit Cu-Fe proteomic association. The protein abundance under copper and iron deduction affected the photosynthetic electronic activity of Synechocystis sp. PCC 6803 and eventually affected the growth and photosynthesis. Based on these results, we hypothesize that the Cu-Fe proteomic association of Synechocystis sp. PCC 6803 can be elucidated via the uptake system of outer membrane-periplasmic space-inner plasma membrane-thylakoid membrane, and this association is mainly required to maintain electron transfer. This study provides a broader view regarding the proteomic association between Cu and Fe in cyanobacteria, which will shed light on the role of these two metal elements in cyanobacterial energy metabolism and biomass accumulation.